2022
DOI: 10.1038/s41598-022-18162-3
|View full text |Cite
|
Sign up to set email alerts
|

Overt and implicit prosody contribute to neurophysiological responses previously attributed to grammatical processing

Abstract: Recent neurophysiological research suggests that slow cortical activity tracks hierarchical syntactic structure during online sentence processing. Here we tested an alternative hypothesis: electrophysiological activity peaks at constituent phrase as well as sentence frequencies reflect cortical tracking of overt or covert (implicit) prosodic grouping. Participants listened to series of sentences presented in three conditions while electroencephalography (EEG) was recorded. First, prosodic cues in the sentence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 75 publications
1
18
1
Order By: Relevance
“…While we suggest above that the increased phrase band ITPC may index the formation of type‐based syntactic constituents, others have shown that such responses may also be generated by neural processes related to prosody (Boucher et al, 2019; Glushko et al, 2022). For example, Boucher et al reported that auditorily presented French clauses and pseudoword sequences elicited comparable delta ITPC when matched for prosody, while less ITPC was elicited by prosodically matched nonspeech tones.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…While we suggest above that the increased phrase band ITPC may index the formation of type‐based syntactic constituents, others have shown that such responses may also be generated by neural processes related to prosody (Boucher et al, 2019; Glushko et al, 2022). For example, Boucher et al reported that auditorily presented French clauses and pseudoword sequences elicited comparable delta ITPC when matched for prosody, while less ITPC was elicited by prosodically matched nonspeech tones.…”
Section: Discussionmentioning
confidence: 51%
“…Because their pseudoword sequences did not obviously correspond to syntactic structures, the authors suggested that low‐frequency ITPC likely arises from processing acoustic chunks corresponding to speech‐specific prosodic boundaries, rather than syntactic processes. There is also evidence that phase synchrony may arise from implicitly generated prosodic boundaries, even when these markers do not necessarily correspond with the closure of syntactic constituents (Glushko et al, 2022). Accordingly, we cannot entirely reject the possibility that the increased phrase band ITPC reported here was driven (at least in part) by prosodic information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus possible to hypothesize that the regular interaction between and co-occurrence of these two linguistic features has driven the brain into expecting syntactic and prosodic representations to be coherent even if one of the two is not explicitly present, or when they do not co-occur. In line with this, a recent study has demonstrated that the cortical tracking of naturalistic speech is enhanced when overt and covert prosodic boundaries are aligned with the syntactic structure compared to when they are misaligned 34 .…”
Section: Introductionmentioning
confidence: 58%
“…Second, listeners perceive prosodic breaks at syntactic boundaries even when no acoustic cue for such a break exists (Buxó-Lugo & Watson, 2016; Cole et al, 2010). Thus, it is possible that delta-band neural speech tracking reflects some type of prosodic processing nonetheless (Gilbert et al, 2015; Glushko et al, 2022; Henke & Meyer, 2021).…”
Section: Introductionmentioning
confidence: 99%